White collar and financial crimes : a casebook of fraudsters, scam artists, and corporate thieves - Noble, Jennifer C. (Oakland, California : University of California Press, 2021)
"Examining a shocking array of fraud, corruption, theft, and embezzlement cases, this vivid collection reveals the practice of detecting, investigating, prosecuting, defending, and resolving white-collar crimes. Each chapter is a case study of an illustrative criminal case and draws on extensive public records around obscure and high-profile crimes of the powerful, such as money laundering, mortgage fraud, public corruption, securities fraud, environmental crimes, and Ponzi schemes. Organized around a consistent analytic framework, every case tells a unique story and provides an engaging introduction to these complex crimes, while also introducing students to the practical aspects of investigation and prosecution of white-collar offenses. Jennifer Noble's text takes students to the front lines of these vastly understudied crimes, preparing them for future practice and policy work"--
Embezzlement -- Mortgage fraud -- Ponzi schemes -- Healthcare fraud -- Cybercrimes -- Corporate fraud -- Money laundering -- Environmental crimes -- Foreign Corrupt Practice Act -- Insider trading -- Academic fraud -- False advertising
Includes bibliographical references and index.
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: White collar crimes -- United States -- Case studies; Commercial crimes -- United States -- Case studies; Swindlers and swindling -- United States -- Case studies; Deceptive advertising -- United States -- Case studies; Computer crimes -- United States -- Case studies